Equity research on intercontinental hotels group PLC - how to feel safe in the hotel industry - Bento, Sofia Belo dee Sousa (2022)
This report contains the valuation conducted to InterContinental Hotel Group PLC, one of the largest Hotel Chains worldwide. This study includes analyses made to macroeconomic, industry, and company-specific factors that may have any impact on the company’s value. It also includes scenario and sensitivity analysis regarding the uncertainties that the global pandemic brought to the economy. An estimated share price was computed, which prompts us to recommend investors to hold their positions on InterContinental Hotel Group.